Cellular stress from excitatory neurotransmission contributes to cholesterol loss in hippocampal neurons aging in vitro - Sodero, Alejandro Omar (2011)
After approximately 3 weeks in vitro, hippocampal neurons present many of the typical hallmarks accompanying neuronal aging in vivo, including accumulation of reactive oxygen species (ROS), lipofuscin granules, heterochromatic foci, and activation of the Jun N-terminal protein kinase (pJNK) and p53/p21 pathways. In addition, hippocampal neurons in vitro undergo a gradual loss of cholesterol, which is important for the activation of the prosurvival tyrosine kinase receptor TrkB. Here, we used the hippocampal in vitro system to investigate the possible cause of age-accompanying cholesterol loss. We report that cholesterol loss during in vitro aging is paralleled by upregulation and translocation to the neuronal surface of cholesterol-24-hydroxylase (Cyp46), the enzyme responsible for cholesterol removal from neurons. Chronic reduction of electrical activity diminished cholesterol loss in aged neurons and precluded the upregulation of cholesterol-24-hydroxylase. In agreement with a cause-effect relationship, stimulation of excitatory neurotransmission in young neurons led to cholesterol loss. Mechanistically, N-methyl-D-aspartate (NMDA)-mediated excitatory neurotransmission leads to cholesterol loss through generation of reactive oxygen species derived from the activation of the stress-responsive enzyme NADPH oxidase. Supporting the relevance of the in vitro data, reduced cholesterol was also detected in synaptic membranes from old mice brains. Furthermore, excitatory neurotransmission via the nicotinamide adenine dinucleotide phosphate (NADPH)-oxidase pathway induced cholesterol loss in purified brain synaptosomes. The current studies highlight excitatory neurotransmission as 1 of the mechanisms involved in cholesterol loss during aging.